EVALUASI PENGGUNAAN ANTIBIOTIK DENGAN METODE ATC/DDD DAN DU 90% DI PUSKESMAS AUR DURI KOTA JAMBI PERIODE 2016-2018 - Andriani, Yuni; Martua, Aris Sahat; Andriani, Medi (Fakultas Farmasi UMI, 2020)
Introduction: Since 23 years ago, WHO transferred ATC (Chemical Therapeutic Chemical) and DDD (Defined Daily Dose) as a global standard for the study of drug use, one of which is antibiotics. Drug Use Method 90% (DU 90%) method that shows the grouping of drugs that fall into the 90% category of use that is often used in conjunction with an analysis of the use of ATC / DDD drugs. Research Objectives: determine the use of antibiotics in Aur Duri Health Center in Jambi City based on the ATC / DDD method and DU 90% for the 2016-2018 period. Research Methods: Retrospective data collection using ATC / DDD and DU 90% methods. Results: Of the four types of antibiotics, the highest DDD value was obtained at Aur Duri Health Center for the period of 2016-2018, namely amoxicillin antibiotics. Antibiotics that entered the DU 90% segment at Aur Duri Health Center based on data for the 2016-2018 period were amoxicillin, ciprofloxacin and tetracycline. The most quantitative data using the ATC / DDD method is amoxicillin with the highest number of 39.39 DDD / 1000 KPRJ / Year in Aur Duri Puskesmas in 2017.